Effects of surface coordination of atoms on the surface properties of Cd-X (X= Ga, Zn) liquid alloys - Koirala, Ishwar (Himalayan Journal of Science and Technology, 2018)
We have investigated the effect of surface coordination of atoms on the surface properties of Cd-Ga and Cd-Zn liquid alloys by varying their surface coordination fractions using statistical mechanics model. Surface tension and surface concentration did not have significant effect on the calculation of both surface tension and surface concentration of two alloys. The computation of the concentration fluctuations at the surface revealed that it was sensitive to the surface coordination fractions of both segregating systems. In those alloys we found that the computation of the Warren-Cowley short rang order parameter was influenced by the surface coordination fractions.